IMPLEMENTATION EVALUATION OF MINIMUM STANDARD OF URBAN SETTLEMENT USING MANN WHITNEY TEST - Ridayati, Ridayati (Jurnal Teknologi, 2018)
The development of tourism and education activities has become one of the factors triggering the rapid urban physical development in Yogyakarta. Construction of hotels, apartments, and middle to upper class housings has triggered increases in land price in the surrounding area. The purpose of this study was to identify the characteristic of land transacted in urban areas in Ngaglik sub-district from 2008 to 2016. Based on Governor Regulation Number 11 of 2007, there is a minimum lot size regulation imposed for housing development in Sleman. The data of land transaction during the period of 2008- 2016 was analyzed using crosstab and Mann Whitney Test. The results of this study showed that 129 urban lands were transacted. The area of ​​land transacted in urban areas which meets the requirements of the governor regulation reaches 114 or about 88.4%. The test showed that there is a significant difference between the area of ​​land transacted in urban areas and in rural areas.